Gamified.: a study of gamification in user experience design - Chang, Wilson Jon Yao (Nanyang Technological University, 2023)
This project explores different qualities of user experience (UX) of gamification in design through conducting a design research study. Specifically, I am exploring how designers can improve the user experience of any project they work on by implementing gamified concepts or game design theories without invoking unethical designs such as addictive practices or forceful engagement.